2023
DOI: 10.1002/cta.3577
|View full text |Cite
|
Sign up to set email alerts
|

A low settling time switching scheme for SAR ADCs with reset‐free regenerative comparator

Abstract: Summary This paper presents an energy‐efficient fully differential switching scheme for successive approximation register (SAR) analog‐to‐digital converters (ADCs). During the sampling phase, the top and bottom plates of all capacitors except most significant bit (MSB) capacitors are grounded in digital‐to‐analog converter (DAC) arrays. The input signals are bottom plate sampled on MSB capacitors. This technique can reduce the settling time by more than 87.5% in comparison with the conventional switching schem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In applications like telecommunications, multimedia processing, sensor networks, and measurement systems where accurate and dependable conversion of analog signals is necessary, high-resolution ADCs are essential. These ADC's offer a way to precisely represent analog data in digital form, al-lowing for effective information processing, storage, and transfer [3,4]. The SAR ADC architecture is a preferred option for high-speed applications due to its widespread recognition of efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In applications like telecommunications, multimedia processing, sensor networks, and measurement systems where accurate and dependable conversion of analog signals is necessary, high-resolution ADCs are essential. These ADC's offer a way to precisely represent analog data in digital form, al-lowing for effective information processing, storage, and transfer [3,4]. The SAR ADC architecture is a preferred option for high-speed applications due to its widespread recognition of efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In the energy consumption analysis of the SAR ADC, it was learned that the capacitor array DAC consumed about 30% of the overall energy consumption [ 7 , 8 , 9 ], while the simulation energy analysis of the chip found that the DAC’s energy consumption was closer to 70% of the total energy consumption [ 10 , 11 , 12 ], coupled with the fact that it was relatively difficult to improve the structure of the analog module circuit.…”
Section: Introductionmentioning
confidence: 99%
“…Although this comparator has an easy-to-design structure, it consumes a considerable current at the evaluation phase, especially with low input common-mode voltages. Furthermore, it has a limited common-mode range which is important for many applications like successive approximation register analog to digital converters (SAR ADCs) [2]. A rail-to-rail operation is achieved by applying a bulk-driven technique at the expense of low energy efficiency [3].…”
Section: Introductionmentioning
confidence: 99%